2015
DOI: 10.1007/s10597-015-9927-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Care Providers’ Views of Their Work with Consumers and Their Reports of Recovery-Orientation, Job Satisfaction, and Personal Growth

Abstract: The research examined the role of mental health care providers' perceptions of their professional relationships with consumers in understanding their reports of agency recovery-oriented services and their own sense of job satisfaction and personal growth. Multidisciplinary community mental health care providers (N = 105) responded to an online self-report questionnaire. Providers' reports of higher levels of working alliance and greater provider directiveness in working with consumers was significantly related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
(49 reference statements)
3
24
0
1
Order By: Relevance
“…Concerning team processes, the concentration of high scores among the Metropolitan and Urban networks: senior medical professionals" (category 2) and low scores among "Metropolitan network: psychosocial professionals" (category 1) was logical, as these variables are often strongly related even though they measure distinct concepts. Previous studies have identified associations between job satisfaction and team collaboration [75], involvement in the decision-making process [76], team autonomy [77], recovery-oriented services [78] and lower conflict between co-workers [76]. Associations were also found between team interdependence, team support and work role performance [17,79].…”
Section: Discussionmentioning
confidence: 95%
“…Concerning team processes, the concentration of high scores among the Metropolitan and Urban networks: senior medical professionals" (category 2) and low scores among "Metropolitan network: psychosocial professionals" (category 1) was logical, as these variables are often strongly related even though they measure distinct concepts. Previous studies have identified associations between job satisfaction and team collaboration [75], involvement in the decision-making process [76], team autonomy [77], recovery-oriented services [78] and lower conflict between co-workers [76]. Associations were also found between team interdependence, team support and work role performance [17,79].…”
Section: Discussionmentioning
confidence: 95%
“…Teamwork also enhances the quality of interdependence (Chiocchio, 2012; McIntyre & Salas, 1995). Regarding recovery promotion and WRP, reports indicate that more effective recovery-oriented services lead to less burnout and higher job satisfaction, two mediators of WRP among MHPs (Osborn & Stein, 2016). Other studies (Lakeman, 2010; Williams & Tufford, 2012) with service users have suggested that recovery-oriented care requires MHPs to possess specific knowledge (e.g., information about illness and treatment and access to services) and skills (e.g., teamwork, coordination, and collaboration).…”
Section: Discussionmentioning
confidence: 99%
“…As Osborn and Stein (2016) state, moving from total institutions to community-based services Bneeds to be accompanied by a larger shift in professional culture regarding what it means to be a professional helper^(765).…”
Section: Beyond Rules and Regulationsmentioning
confidence: 99%